Marketing Strategy of Lembaga Tabung Haji A Case Study - A. Rahman, Mahfar (1998)
The approach in marketing of services has been changing nowadays. In concept, services are marketed in the same way as tangible goods. In practice however, the characteristics that differentiate services from goods lead to different marketing program. The strategies and tactics used in the marketing of goods frequently are not appropriate for services marketing. This paper would study the practice of marketing of services at Lembaga Tabung Haji (LTH). It would be preceded by the historical background and operational aspects as well as marketing strategy practiced by LTH in the first part. The analysis, comments and recommendations would be covered in the second part.